INTEGRATIVE MANAGEMENT OF COCOA AGROFORESTRY SYSTEMS: PROMOTING LONG-TERM ON-FARM DIVERSITY (Journal of Science and Technology, 2016)
In cocoa (Theobroma cacao) agroforestry systems, upper canopy trees and food crops are frequently planted for shade, diversification of farm products, and improved soil fertility. As diversification remains a top priority for farm economic and environmental sustainability, system management plays a substantial role in farm diversity, requiring long-term analysis.  We measured species richness dynamics in a chronosequence (N = 4) representing farms aged 2 to 25 years old in the western cocoa-growing region of Ghana, West Africa.  Subsequently, we conducted farmer interviews to establish farming practices with regards to integration of non-cocoa species. After farm establishment, increases were recorded in non-cocoa and Simpson diversity index (for 2 years = 0.17 ± 0.167; for 15 years = 0.68 ± 0.026; for 25 years = 0.68 ± 0.036), but no changes were observed in crop richness. All participants interviewed managed supplementary species on their cocoa farms, with 92% of farmers purposefully establishing an upper canopy stratum. We discuss the use of principles from natural stand development for sustaining such diversity. Farmer managed crop re-initiation during farm maturation may promote higher diversity within an existing agroforestry framework.